Use of a geospatial early-warning decision support system to prepare for disasters or plan for multiple hazards: decatastrophize - Damalas, Andreas; Mettas, Christodoulos; Evagorou, Evagoras G.; Papadopoulos, Marinos; Konstantinou, Alexia; Hadjimitsis, Diofantos G. (My University, 2017)
The goal of DECATASTROPHIZE (DECAT) is to use a Geospatial Early-warning Decision Support System (GE-DSS) for rapid deployment, interoperability, transferability and sustainability to assess, prepare for and respond to multiple and/or simultaneous natural and man-made hazards, disasters, and environmental incidents by using existing models/systems in a synergistic way on one multiplatform, distributed and integrated framework called DECAT in five partner countries. The use of GE‐DSS combined with integrated Geographic Information System (GIS) solutions fuses text and geographic information into one model and view. In addition to integrating the a) GE‐DSS, b) Emergency Operation Centres (EOCs), and c) Operational Resources (OR) in the field in each partner country, the DECAT methodological framework software will also integrate hazard/risk assessment with the common operational picture. No studies using a GE‐DSS based framework to integrate and link decision makers, EOCs and ORs in the field for multi‐hazard or disaster preparedness in accordance with/relative to the New EU Civil Protection Mechanism preparedness priorities have been carried out or demonstrated. Therefore, this project is expected to a) create better prerequisites for, and improve preparedness, as well as enhance awareness of, civil protection and/or marine pollution professionals and volunteers, b) support and complement the efforts of the participating states for the protection of citizens, environment and property in the event of natural and man‐made disasters, c) exchange information, experience, good practice and knowledge aimed at improving the performance of parties involved in civil protection (both private and public professionals and volunteers) and d) support the EU candidate countries and potential candidates not participating in the Mechanism and European Neighbourhood Policy countries in the field of disaster preparedness and enhance their cooperation within the Union Civil Protection Mechanism and its participating states.
Keywords: Disaster management; Disaster preparedness; Geospatial early warning decision support system (GE-DSS); Humanitarian aid and civil protection (ECHO)